ADAMTS-7 Inhibits Re-endothelialization of Injured Arteries and Promotes Vascular Remodeling Through Cleavage of Thrombospondin-1. Issue 13 (31st March 2015) - Kessler, Thorsten; Zhang, Lu; Liu, Ziyi; Yin, Xiaoke; Huang, Yaqian; Wang, Yingbao; Fu, Yi; Mayr, Manuel; Ge, Qing; Xu, Qingbo; Zhu, Yi; Wang, Xian; et al.
Abstract : Background—: ADAMTS-7, a member of the disintegrin and metalloproteinase with thrombospondin motifs (ADAMTS) family, was recently identified to be significantly associated genomewide with coronary artery disease. However, the mechanisms that link ADAMTS-7 and coronary artery disease risk remain elusive. We have previously demonstrated that ADAMTS-7 promotes vascular smooth muscle cell migration and postinjury neointima formation via degradation of a matrix protein cartilage oligomeric matrix protein. Because delayed endothelium repair renders neointima and atherosclerosis plaque formation after vessel injury, we examined whether ADAMTS-7 also inhibits re-endothelialization. Methods and Results—: Wire injury of the carotid artery and Evans blue staining were performed in Adamts7 –/– and wild-type mice. Adamts-7 deficiency greatly promoted re-endothelialization at 3, 5, and 7 days after injury. Consequently, Adamts-7 deficiency substantially ameliorated neointima formation in mice at days 14 and 28 after injury in comparison with the wild type. In vitro studies further indicated that ADAMTS-7 inhibited both endothelial cell proliferation and migration. Surprisingly, cartilage oligomeric matrix protein deficiency did not affect endothelial cell proliferation/migration and re-endothelialization in mice. In a further examination of other potential vascular substrates of ADAMTS-7, a label-free liquid chromatography-tandem mass spectrometry secretome analysis revealed thrombospondin-1 as a potential ADAMTS-7 target. The subsequent studies showed that ADAMTS-7 was directly associated with thrombospondin-1 by its C terminus and degraded thrombospondin-1 in vivo and in vitro. The inhibitory effect of ADAMTS-7 on postinjury endothelium recovery was circumvented in Tsp1 –/– mice. Conclusions—: Our study revealed a novel mechanism by which ADAMTS-7 affects neointima formation. Thus, ADAMTS-7 is a promising treatment target for postinjury vascular intima hyperplasia. Abstract : Supplemental Digital Content is available in the text.